ПОНЯТИЕ И СОДЕРЖАНИЕ ОЦЕНКИ ЭФФЕКТИВНОСТИ ВЗАИМОДЕЙСТВИЯ СУДЕБНО-ЭКСПЕРТНЫХ УЧРЕЖДЕНИЙ С ПРАВООХРАНИТЕЛЬНЫМИ ОРГАНАМИ - Полянский, Антон Александрович (SUPREMANCE OF LAW, 2017)
In the article, based on the analysis of the scientific views of scientists regarding the interpretation of the concept of “assessment”, the author’s definition of assessing the effectiveness of the interaction of forensic institutions with law enforcement agencies is formed. It was stated that assessment is a very important social tool, including public administration. Attention is focused on the lack of scientific development of the problems presented in the article.
Keywords: assessment; efficiency; interaction; law enforcement agencies; forensic institutions